Cost Leadership versus Differentiation Strategy: Peran Akuntansi Manajemen dalam Menciptakan Keunggulan Kompetitif Perusahaan Manufaktur - Magdalena Pazizi; Mukhtaruddin . (CV. ITTC INDONESIA, 2026)
Competition in Indonesia's manufacturing industry requires companies to implement competitive strategies that can create sustainable competitive advantages. This article aims to examine the role of management accounting in supporting the implementation of cost leadership and differentiation strategies in manufacturing companies in Indonesia. The research uses a qualitative approach with the Systematic Literature Review (SLR) method on relevant scientific journal articles indexed in the SINTA, Garuda, and Google Scholar databases. The results of the study show that the cost leadership strategy focuses on efficiency and cost control, while the differentiation strategy emphasizes value creation through product quality and innovation. The success of both strategies is highly dependent on the ability of management accounting to provide relevant cost and performance information to support planning, control, and strategic decision-making. Management accounting acts as a strategic information system that integrates operational efficiency and value creation, enabling companies to adjust their competitive strategies contextually in accordance with industry characteristics and internal capabilities. Thus, strengthening the management accounting system is an important prerequisite for enhancing the competitive advantage of manufacturing companies in Indonesia.